Paranoid Personality Disorder of the Main Character Seen in Edgar Allan Poe’s A Tale Tell Heart - Ana Widiyanti (Metaphor, 2020)
This study aims at analyzing the paranoid disorder reflected in Poe’s A Tale Tell Heart. The researcher conducts a qualitative research by applying psychological approach. This study uses Freud’s theory to explain the personality of the main character. The finding of the research shows that the main character has a mental disorder in form of personality disorder.The main character perceived paranoid and eventually as paranoid sufferer, the main character commits to be a murderer of another character.